Incidence of chronic pancreatitis in the Czech Republic - Díte, P; Starý, K; Novotný, I; Precechtelová, M; Dolina, J; Lata, J; Zboril, V (European journal of gastroenterology & hepatology, 2001)
There have been only a few studies dealing with the incidence of chronic pancreatitis published. Over the last 80 years, original studies describing the incidence of chronic pancreatitis were undertaken, including studies in Scandinavia, Switzerland, Hungary and Poland. Incidence varied geographically, from 1.6 new cases per year among 100,000 inhabitants in Switzerland to 23 new cases among 100,000 inhabitants in Finland. The aetiology of 70% of all cases was alcoholic pancreatitis. The incidence of chronic pancreatitis in the Czech Republic is 7.9 per 100,000 inhabitants per year, similar to that of Denmark and Germany, but higher than that of Poland or Switzerland. In our study, the main aetiological factor was alcohol (65.4% of all cases, with consumption of alcohol of > 75.0 g/day).
Keywords: dospělí; Sex Distribution; Female; rozložení podle pohlaví; Adult; ženské pohlaví; lidé; Risk Factors; Incidence; Age Distribution; Male; incidence; Aged; Czech Republic; věkové rozložení; rizikové faktory; Pancreatitis; Česká republika; chronická nemoc; lidé středního věku; senioři; mužské pohlaví; pankreatitida; Chronic Disease; Middle Aged; Humans